Economic valuation of ecosystem services in protected areas: A case study from Nepal - KC, B; Kandel, PN; Adhikari, S (Banko Janakari, 2013)
The research examines the value of ecosystem services in Baghmara Buffer Zone Community Forest of Nepal determining willingness of local users and tourists for sustainable management and conservation of natural resources as well as recreational and aesthetic services, during September of 2010. The contingent valuation survey was administered to 95 users and 100 tourists. For users, the distance to forest, family size, nature of residence, gender and size of land holding seem to be the prominent factors that affected upon their willingness to pay. The projected average willingness to pay by all users for recreational and aesthetic services was NRs. 33,347 (about US 460) per year. The tourists were divided into domestic and international to elicit willingness to pay for ecosystem services. The responses were found varied according to the nature of tourists. For domestic tourists, income was only factor that affected their willingness to pay, but for international tourists along with income, gender, travel group and education were major determinants of willingness to pay. The average projected willingness to pay by all tourists was US 3,806,468 per year.The research highlights that the conservation area systems in Nepal has a high potential to generate additional resources against ecosystem services provided additional services to the tourists and a mechanism to tap such contribution. Banko Janakari, Vol. 23, No. 1, Page 42-50 DOI: http://dx.doi.org/10.3126/banko.v23i1.9466